The First-year Integration Test: a validation study - Willems, Jonas; Vanoverberghe, Veerle; Coertjens, Liesje; Donche, Vincent (Frontiers in Psychology, 2023)
To date, there has been little agreement on what important facets should be incorporated in quantitative measures of the academic and social first-year experience. Moreover, such scales are typically developed in academic higher education (HE) contexts (i.e., universities providing more theoretical and scientific education), and are disconnected from the experiences of students in professional HE contexts (i.e., university colleges, offering more vocational education that prepares students for practicing a specific occupation, such as social work). The First-year Integration Test (FIT) is a newly developed instrument that aims to map out students’ perceptions of how they are dealing with their academic and social transition in the first semester of HE, and was based on thorough qualitative research in professional HE. In the present study, the psychometric value of FIT is explored. Results show that FIT has good construct validity, and all scales are internally consistent. Also, evidence was found for the convergent, discriminant and criterion-related validity of the instrument. We argue that FIT holds potential as a tool for generating student feedback, as a monitoring tool within an institution’s quality assurance system, and as a valuable research instrument.